Intuition in Plato and the Platonic tradition. - Gerson, Lloyd P. (British Journal for the History of Philosophy, 2023)
In this paper, I examine what is for Plato and all those who follow in his footsteps the ne plus ultra of cognition, namely, intuition (nous or noēsis). This is the paradigm of cognition, meaning that all forms of human (and even animal) cognition are inferior manifestations of this. Intuition is mental seeing, analogous to physical seeing. Among embodied souls, it is seeing a unity of some sort manifested in some diversity or plurality. Thus, someone who sees that the Morning Star is the Evening Star, or that S at t1 is identical with S at t2, or that f = ma, etc., sees the unity 'behind' the diversity. The disembodied intellect that is the Demiurge (or, for Aristotle, the Unmoved Mover) sees paradigmatically the diversity of all intelligible being as a unity. Because mental seeing or intuition is paradigmatic for all cognition, cognition is essentially a unificatory process. Plato's method of collection and division displays both this process and its reverse. In the light of this core doctrine, I examine some of the insights that Platonists, especially Plotinus and Proclus, arrived at regarding a host of issues, including the nature of the first principle of all and the nature of normativity.